ANALISIS TINGKAT PEMAHAMAN MAHASISWA TEKNIK SIPIL PADA MATA KULIAH FISIKA TERAPAN SELAMA PEMBELAJARAN DARING - Stefany Margareta Martono; VINA N VAN HARLING (LPPM Politeknik Saint Paul Sorong, 2021)
The Covid-19 pandemic that has occurred throughout the world, especially Indonesia, is a situation that requires everyone to work, study and carry out activities from home. In the world of education, the Covid-19 pandemic has had a major influence on learning activities from elementary to high (college) levels, where in the past learning could be done directly but currently requires all teachers, students and students to study online (on a network). Lecturers are required not only in mastering technology as well, but the delivery of material from lecturers also certainly has an important influence on students' understanding of the material. Lecturers must be able to make students understand what is conveyed in online learning. This research was carried out by the Civil Engineering study program at the Catholic Polytechnic of Saint Paul Sorong in the applied physics course. Research data was taken through a questionnaire distributed online to semester 1 students of the 2020/2021 academic year who had taken an online Applied Physics course with a total of 41 students as respondents. This research is descriptive quantitative. This study uses an instrument that is a questionnaire. The contents of the questionnaire relate to how much students are able to understand applied physics courses and student responses during online learning. The questionnaire used has been tested for validity and reliability using the SPSS version 23 application. Based on the research data, it can be concluded that the percentage of students' understanding of civil engineering in applied physics courses during online learning is 43% at most stating that online learning has been going well.